2017
DOI: 10.1007/s11356-017-9251-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thyme powder (Thymus vulgaris L.) supplementation on gene expression profiles of cytokines and economic efficiency of broiler diets

Abstract: This study was conducted in an attempt to evaluate the impact of thyme powder supplementation on broiler diets with respect to cytokine and mucin2 gene expressions. It was also our aim to evaluate the growth performance, blood biochemical and hematological profiles, and economic efficiency of the diet. A total of 120 1-day old chicks (Cobb 500) were divided into four groups on the basis of the diet. One group received a basal diet (control) while the others received a basal diet supplemented with 2, 5, or 8 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
8
21
0
Order By: Relevance
“…The inclusion of EOB in drinking water, of broilers, did not alter (p > 0.05) breast muscle, liver, heart and spleen yields at 42 days of age which is in agreement with the results of Rahimi et al (2011) and Ibrahim et al (2018). In the current study, our findings demonstrated that relative weight of lymphoid organs (bursa of Fabricius and thymus) was increased in response to EOB which was consistent with the findings of Hassan and Awad (2017). Our results regarding the serum lipid profile showed that supplementation of EOB in drinking water decreased the total serum CHOL but did not affect the TG, HDL and LDL concentrations, which was in agreement with other studies (Abdulkarimi et al, 2011;Ibrahim et al, 2018;Mashayekhi et al, 2018;Menati, Ali, & Abidelhuseen, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The inclusion of EOB in drinking water, of broilers, did not alter (p > 0.05) breast muscle, liver, heart and spleen yields at 42 days of age which is in agreement with the results of Rahimi et al (2011) and Ibrahim et al (2018). In the current study, our findings demonstrated that relative weight of lymphoid organs (bursa of Fabricius and thymus) was increased in response to EOB which was consistent with the findings of Hassan and Awad (2017). Our results regarding the serum lipid profile showed that supplementation of EOB in drinking water decreased the total serum CHOL but did not affect the TG, HDL and LDL concentrations, which was in agreement with other studies (Abdulkarimi et al, 2011;Ibrahim et al, 2018;Mashayekhi et al, 2018;Menati, Ali, & Abidelhuseen, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The inclusion of EOB in drinking water, of broilers, did not alter ( p > 0.05) breast muscle, liver, heart and spleen yields at 42 days of age which is in agreement with the results of Rahimi et al () and Ibrahim et al (). In the current study, our findings demonstrated that relative weight of lymphoid organs (bursa of Fabricius and thymus) was increased in response to EOB which was consistent with the findings of Hassan and Awad (). Immune cells develop and proliferate in immune organs, and their status determines the dosage of immune function.…”
Section: Discussionsupporting
confidence: 92%
“…In the jejuna of broilers, supplementation with thyme powder, which contains the essential oils thymol (50.48%), γ-terpinene (11.03%), P-cymene (9.77%), and carvacrol (4.30%), significantly decreased transcriptional factor NFκB. Pro-inflammatory cytokines such as IL-6, IFN-γ, and TNF-α were also downregulated in broilers following treatment with thyme powder [ 119 ]. This is consistent with previously mentioned results, suggesting that the anti-inflammatory effects of thyme make it suitable for application in animal production.…”
Section: Interactions Between Phytochemicals and The Mapk- And Nfκb-rmentioning
confidence: 99%
“…Economic efficiency = net return per kg gain/feed cost per kg gain (Hassan & Awad, 2017). Economic efficiency = net return per kg gain/feed cost per kg gain (Hassan & Awad, 2017).…”
Section: Returnmentioning
confidence: 99%